Collaborative Governance dalam Pengembangan Desa Wisata Berbasis Ekowisata di Ekowisata Nologaten - Lasampa, Yelky Rudolf; Ardiyati, Ardiyati (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to analyze the application of collaborative governance in developing Nologaten's Ecotourism, a tourist area located in RW 04, Nologaten, Caturtunggal, Sleman Regency. This area was previously a slum on the banks of the Gajah Wong River, but has been successfully revitalized through the City Without Slums (Kotaku) program since 2017. The research uses a qualitative approach with a case study method, involving eight informants from elements of the village government, ecotourism managers, and the community. Data were collected through in-depth interviews, direct observations, and documentation, then analyzed using thematic analysis techniques. The study results show that the development of Nologaten Ecotourism involves multi-stakeholder collaboration with structured roles, facilitative leadership, and a strong communication and trust-building process. This collaboration promotes environmental conservation, cultural conservation, and local economic improvement, although there are still challenges in waste management and tourism promotion. This study concludes that collaborative governance is an effective approach in realizing participatory and community-based sustainable tourism governance. This finding is expected to be a reference for the development of other tourist villages in Indonesia.